Wireless Power Transfer by Using Solar Energy - M. Fareq; M. Fitra; M. Irwanto; Syafruddin HS; N. Gomesh; M. Rozailan; M. Arinal; Y.M. Irwan; J. Zarinatul (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2014)
This project is based on how to transmit electrical power without wires, using solar energy as source. The power is transferred wirelessly through an inductive coupling method. With this new discovery, we no longer need complicated with the cable passing around us, with Power without Wires (Wireless Electricity) we can use our electronic equipment such as TV, MP3 Player, HiFi Headset; everything works without the use of batteries or electrical wiring. In fact, mobile devices such as laptop batteries, mobile phone, or digital camera filled automatically, so once you enter the house, of course without having to plug in the cable. The project is offer to study and fabricate wireless power transfer by using inductive coupling. Experiments have been conducted and the wireless power transfer using inductive coupling can be transfer energy up to 10 cm.